A Picture Worth a Thousand Texts? Investigating the Influences of Visual Appeals in a Text Message-Based Health Intervention. Issue 3 (3rd March 2020) - Niu, Zhaomeng; Jeong, David C.; Brickman, Jared; Nam, Yujung; Liu, Shuang; Stapleton, Jerod L.
Abstract : Healthy eating among young people may curb obesity and improve health, but strong messaging is needed for healthy eating interventions. In the current work, we evaluated the usefulness of visual appeals in a pilot text message-based healthy eating intervention among college students. A 2 (gain vs. loss) × 2 (image vs. no image) design with pretest and posttest questionnaires (N = 111) revealed text-only messages with loss frames had an influence on affective risk response, while both gain- and loss-framed text messages with visual appeals had positive effects on attitudes and intentions. This pilot study provides evidence to support the feasibility of using visual appeals in text message-based health interventions. The implications of the current study are discussed.